Ototoxicity After Childhood Cancer - Tillmanns, Amélie; Lanvers-Kaminsky, Claudia; Parfitt, Ross; Meijer, Annelot; Tóth, Miklós; Münscher, Adrian; Beck, Johannes; van den Heuvel-Eibrink, Marry; am Zehnhoff-Dinnesen, Antoinette (Springer International Publishing, 2020)
Ototoxicity (i.e., toxic damage to the ear) is a side effect of many drugs that are used in cancer treatment, including anticancer drugs and co-medication such as aminoglycoside antibiotics, glycopeptide antibiotics, macrolides, nonsteroidal anti-inflammatory drugs, loop diuretics, ototopical medication, and cranial irradiation, among others. Aminoglycosides and platinum-based chemotherapy agents are of greatest concern as they often lead to permanent ototoxicity. Ototoxic drugs can have severe short- and long-term effects on patients’ hearing and balance systems, such as impaired speech perception, which impedes language development, psychosocial development, educational attainment, employment prospects, and quality of life. Oncology professionals must balance the benefits of any planned drug treatment against these potential effects. Susceptibility to ototoxic effects is defined by genetic and non-genetic risk factors, such as age or other concomitant ototoxic treatment. Various subjective and objective audiological tests can be used to identify ototoxicity in individual patients, such as pure-tone or play audiometry alongside otoacoustic emissions (OAEs) and auditory brainstem response (ABR) testing. The pros and cons of diagnostic audiological practice, treatment options, and current research into otoprotective medication are discussed in this chapter.
CRIS-Team Scopus Importer:2024-12-16